Low-Intensity Pulsed Ultrasound Modulates RhoA/ROCK Signaling of Rat Mandibular Bone Marrow Mesenchymal Stem Cells to Rescue Their Damaged Cytoskeletal Organization and Cell Biological Function Induced by Radiation - Rong Zhang; Zhaoling Wang; Guoxiong Zhu; Gaoyi Wu; Qingyuan Guo; Hongchen Liu; Lei Chen (Stem Cells International)
Osteoradionecrosis of the jaw (ORNJ) is an infrequent yet potentially devastating complication of head and neck radiation therapy. Low-intensity pulsed ultrasound (LIPUS) has been widely accepted as a promising method for the successful management of ORNJ, but the mechanism remains unclear. In this study, the effects of LIPUS on cytoskeletal reorganization, cell viability, and osteogenic differentiation capacity of rat mandible-derived bone marrow mesenchymal stem cells (M-BMMSCs) induced by radiation were determined by immunofluorescence staining, CCK-8 cell proliferation assay, quantification of alkaline phosphatase (ALP) activity, alizarin red staining, and real-time RT-PCR, respectively. Moreover, the involvement of the RhoA/ROCK signaling pathway underlying this process was investigated via western blot analysis. We found that radiation induced significant damage to the cytoskeleton, cell viability, and osteogenic differentiation capacity of M-BMMSCs and downregulated their expression of RhoA, ROCK, and vinculin while increasing FAK expression. LIPUS treatment effectively rescued the disordered cytoskeleton and redistributed vinculin. Furthermore, the cell viability and osteogenic differentiation capacity were also significantly recovered. More importantly, it could reverse the aberrant expression of the key molecules induced by radiation. Inhibition of RhoA/ROCK signaling remarkably aggravated the inhibitory effect of radiation and attenuated the therapeutic effect of LIPUS. In the light of these findings, the RhoA/ROCK signaling pathway might be a promising target for modifying the therapeutic effect of LIPUS on osteoradionecrosis.